Pengaruh Kompetensi dan Motivasi Arsiparis Terhadap Archival Organization Agility pada Perguruan Tinggi Negeri Badan Hukum Universitas Negeri Semarang - Febrianto, Eko; Kuswantoro, Agung; H., Rina Lilla; S., Andika R. (Perpustakaan dan Arsip Universitas Gadjah Mada, 2024)
All organizations face a competitive, rapidly changing and complex environment, and archival organizations are no different. The strategy that is often implemented by organizations or institutions is agile or nimble organizations or often called archival organization agility. In archival organization agility there are at least two influencing factors, namely competence and motivation. The aim of this research is to determine the influence of competence and motivation on archival organization agility. The scope of this research is the archival organization at Semarang State University with archivists as the research object. This research method uses a quantitative descriptive analysis method of causality with regression analysis. The results of the research concluded that: (1) The competence of archivists at the State University of Legal Entity, Semarang State University has a positive and significant influence on archival organization agility by 97%; (2) The motivation of archivists at the State University of Legal Entity, Semarang State University has a positive and significant influence on archival organization agility by 97%; (3) The competence and motivation of archivists at the State University of Legal Entity, Semarang State University positively and significantly influences archival organization agility by 98%.